Environmental lead exposure among preschool children in Shanghai, China: blood lead levels and risk factors. - Jia Cao; Minming Li; Yu Wang; Guangjun Yu; Chonghuai Yan (PLoS ONE)
Objective To determine blood lead levels and to identify related risk factors among children in Shanghai; to explore the lead change trend of children after industrial transformation and to provide data for policy development to control environmental lead pollution in Shanghai. Methods A stratified-clustered-random sampling method was used. A tungsten atomizer absorption spectrophotometer was employed to determine blood lead levels. Results The arithmetic mean, geometric mean and median of blood lead levels of 0- to 6-year-old children from Shanghai were 22.49 µg/L, 19.65 µg/L and 19.5 µg/L, including 0.26% (6/2291) with concentrations ≥100 µg/L and 2.7% (61/2291) with concentrations ≥50 µg/L. Boys' levels (23.57 µg/L) were greater than those of girls (21.2 µg/L). The blood lead levels increased with age. This survey showed that the Chongming district was the highest and Yangpu district was the lowest, this result is completely opposite with the earlier survey in Shanghai. Risk factors for lead contamination included housing environment, parents' education levels, social status, hobbies, and children's nutritional status. Conclusions The blood lead levels of children in Shanghai were lower than the earlier data of Shanghai and those of published studies in China, but higher than the blood lead levels of developed countries. The blood lead levels of urban districts are higher than the central districts with the industrial transformation. Society and the government should take an active interest in childhood lead poisoning of urban areas.